Liquidity planning - Mirza, Baber (2017)
This report is based on the internship activities I performed at Robert Bosch Benelux (RBBN), from 26th September 2016 to 31st March 2017. This firm is one of the regional organization of Robert Bosch GmbH. Robert Bosch GmbH is a private multinational company engaged in the development of engineering and electronics product. The Bosch Group is composed of four major business sectors, named mobility solutions, industrial technology, consumer goods and energy and building technology. Bosch Group desires to enrich the quality of life with solutions that are both innovative and beneficial. The company concentrates their core competencies in automotive and industrial technologies. Bosch is also contributing in the production of products and services for professional and private use. My exposure at Bosch proved to be extremely fruitful. I gained valuable cultural, practical and professional experience. In my role as an assistant controller, my financial expertise developed exponentially. I am a quick learner thus I adapted to the changing needs of the controlling and finance department with perfect ease. I learnt the importance of deadlines, teamwork and effectively coordinating in a fast-paced environment. This traineeship resulted in providing me with a platform to advance my professional prospects. This report attempts to fulfil one specific requirement of Robert Bosch Benelux, which was with regards to liquidity planning. Liquidity planning is essential for the survival and prosperity of any business and it is the foremost gauge of a company’s financial health. The significance of cash flow in business is often compared to the human anatomy and its constant need for oxygen. Therefore to gain enhanced understanding of its cash flow Robert Bosch Benelux provided me with an opportunity to devise a cash flow forecasting methodology. My foremost contribution towards this project was the development of new forecasting strategy for the core cash flows of Robert Bosch Benelux. I developed distinctive forecasting strategy to estimate forecasted account receivables, account payables, salaries, payroll taxes and value added tax. The old forecasting methodology was completely discarded due to the fact that new forecasting methodology was superior. I arrived at this conclusion after a comparison of the old and new methodology, proven through a percentage forecast error formula. In conclusion, the new methodology presented significantly improved results, relatively to the old forecasting methodology at Bosch.